Ocean response to typhoons in the western North Pacific: Composite results from Argo data. (May 2017) - Lin, Sheng; Zhang, Wen-Zhou; Shang, Shao-Ping; Hong, Hua-Sheng
Abstract: Composite structures of ocean temperature and salinity anomalies caused by tropical cyclones (TCs) or typhoons in the western North Pacific Ocean were obtained from Argo data. These structures were used to analyze ocean responses to typhoons and the dynamic mechanisms inherent in those responses with a particular focus on upwelling. TC-induced cooling is often strongly rightward-biased in the surface layer, and shifts toward the typhoon track at depths exceeding roughly 100 m. In the central water column within approximately 75 km of the typhoon track, subsurface warming predicted by vertical mixing is restrained and replaced by cooling due to upwelling. Upwelling contributes 15% on average to temperature cooling in the near surface layer (10–30 m), 84% in the subsurface layer (30–250 m) and 94% in the deep layer (250–600 m) during the period of 0.5–2.5 days after the typhoon's passage. It is suggested that the sea surface cooling effect of vertical mixing can be enhanced by the upwelling. The effect of upwelling is also prominent in the salinity response to typhoons. The composite results from the Argo data clearly reveal basic ocean responses to typhoons and indicate the important role of upwelling therein. Highlights: Ocean responses to typhoons are synthesized from Argo data. Relative importance of upwelling in ocean responses to typhoons is evaluated. Upwelling plays an important role in ocean responses to typhoons.